2021
DOI: 10.1101/2021.09.10.21262710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody responses to BNT162b2 mRNA vaccine: infection-naïve individuals with abdominal obesity warrant attention

Abstract: Objective. The excess of visceral adipose tissue might hinder and delay the immune response. How people with abdominal obesity will respond to mRNA vaccines against SARS-CoV-2 is yet to be established. We evaluated SARS-CoV-2-specific antibody responses after the first and second dose of the BNT162b2 mRNA vaccine comparing the response of individuals affected by abdominal obesity (AO) to those without, discerning between individuals with or without prior infection. Methods. IgG neutralizing antibodies against … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…In our study, the seroconversion rate of patients in the non-prior SARS-CoV-2 infection arm was 83.5% in the obese group and 99.4% in the nonobese group. In a recent study with BNT162b2 mRNA vaccine, the antibody titer in individuals with abdominal obesity was found to be 2.4 times lower than those without [32]. In our study, antibody levels of nonobese subjects were found to be approximately 10 times higher than those of PwO.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, the seroconversion rate of patients in the non-prior SARS-CoV-2 infection arm was 83.5% in the obese group and 99.4% in the nonobese group. In a recent study with BNT162b2 mRNA vaccine, the antibody titer in individuals with abdominal obesity was found to be 2.4 times lower than those without [32]. In our study, antibody levels of nonobese subjects were found to be approximately 10 times higher than those of PwO.…”
Section: Discussioncontrasting
confidence: 50%
“…Of these individuals, 1869 were obese. Out of 12 articles, four [25][26][27]34 articles reported the mRNA vaccines (BNT162b2): two 28,35 that of adenovirus-vector vaccines (ChAdOx1 nCoV-19) and two 29,31 that of inactivated virus vaccines (Sinovac, Sinopharm). The remaining four [31][32][33] articles do not exclusively contain one type of vaccine.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Among the five included articles, three [25][26][27] reported BNT162b2 mRNA vaccination, and two 28,35 were vaccinated with ChAdOx1 nCoV-19 vaccine. As the results show, both vaccinations were significantly associated with obesity (Figure 3A).…”
Section: Relationship Between Obesity and Antibody Titers Of Covid-19...mentioning
confidence: 99%
“… [21] In contrast, a study that categorised by abdominal obesity rather than BMI found those with abdominal obesity had both lower spike antibodies and faster antibody waning in the months following vaccination. [22] It is possible that the distribution of body fat, rather than BMI, may be a stronger predicter of vaccine response. Data on whether obese people in clinical trials or observational studies were vaccinated with needles sufficiently long to ensure intra-muscular deposition are lacking.…”
Section: Discussionmentioning
confidence: 99%